Morphology and anatomy of the vegetative organs and scapes from Aphorocaulon (Paepalanthus, Eriocaulaceae) - Scatena, Vera Lúcia [UNESP]; Rosa, Michele Marcelino [UNESP] (Brazilian Archives of Biology and Technology, 2001)
Estudou-se a anatomia de raízes, caules, folhas e escapos de espécies de Paepalanthus subseção Aphorocaulon. Estas plantas apresentam caules reduzidos com folhas em roseta, de onde crescem os paracládios (sistemas de inflorescências). As espécies apresentam raízes com epiderme unisseriada e córtex com células isodiamétricas. Tanto os caules reduzidos como os paracládios apresentam espessamento resultante da atividade do periciclo, denominado Meristema de Espessamento Primário (MEP). Ambos apresentam estrutura anatômica semelhante. Os escapos apresentam endoderme descontínua, periciclo sinuoso, o córtex apresenta costelas salientes (5-6). As folhas apresentam células epidérmicas alongadas no sentido longitudinal com paredes levemente espessadas, estômatos somente na face abaxial, com câmara subestomática especializada, feixes vasculares colaterais com bainha dupla. Essas estruturas anatômicas são comuns para as espécies da subseção Aphorocaulon. Algumas características anatômicas observadas nestas espécies são típicas de plantas que crescem nos campos rupestres.

The roots, stems, scapes and leaves anatomy of species of Paepalanthus subsect. Aphorocaulon were studied. The plants showed short stems with rosulate leaves and possessed an aerial axis branching, the paraclades. These species had roots with uniseriate epidermis and cortex with isodiametric cells. Short stems and paraclades presented a thickening resulting from the activity of the pericycle named prymary thickening meristem (PTM). They presented a similar anatomical feature. The scapes presented discontinuous endodermis, sinuous pericycle, and the cortex had proeminent ribs (5-6) and the leaves showed epidermis with elongated cells in the longitudinal orientation, cell walls slightly thickened, stomata present only on the abaxial surface, with special leaf substomatal chambers, collateral vascular bundles with a double sheath. Those anatomical characteristics are common to Aphorocaulon species and are those typical of plants that grow in the rupestrian field habitats.
Keywords: Morphology; anatomy; Paepalanthus; Aphorocaulon